PPM FOSTERING INNOVATION MELALUI CONSUMER BEHAVIOR DI TOKO KRUPUK RISMA KOTA SURABAYA - Asep Heryyanto; Muzakki Muzakki (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
Abstract The Community Service Program (PPM) is carried out at the Krupuk Risma Store located around Sukolilo, Kenjeran, Surabaya City. In the implementation of the production field, several problems faced by cooperation partners were obtained, namely: 1) Product quality is sometimes inconsistent; 2) A larger scraping device is needed; 3) Cleanliness around the store; 4) Online marketing is not running optimally; 5) Do not promote outside the Kenjeran area; 6) The recording of financial reports is still manual; 7) Suboptimal financial policy. This community service was carried out for two times, the first was an increase in online sales strategies and the second assistance was an increase in the quantity and quality of production of goods. In addition, community service also provides an active role in the field of cleanliness and acceleration of the payment transaction process. The results of this community service are in accordance with success indicators, namely 1) Partner understanding of product quality control; 2) Partner's understanding of product quantity maximization; 3) Development of sales in the marketplace; 4) Online marketing business; 5) Increased promotion through the cooperation of the city government; 6) Automatic recording of financial statements; 7) Training in decision-making literacy for policy implementation. Based on the questionnaire provided, it showed that the results of the level of understanding of community empowerment partners reached 75% at the Level of Very Understanding, 15% at the level of understanding, and 10% at the level of not understanding. Keyword: Fostering Innovation, Consumer Behavior, MSMEs